2004
DOI: 10.3201/eid1002.030761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Description of a Completed Outbreak of SARS in Vietnam, February–May, 2003

Abstract: We investigated the clinical manifestations and course of all probable severe acute respiratory syndrome (SARS) patients in the Vietnam outbreak. Probable SARS cases were defined by using the revised World Health Organization criteria. We systematically reviewed medical records and undertook descriptive statistical analyses. All 62 patients were hospitalized. On admission, the most prominent symptoms were malaise (82.3%) and fever (79.0%). Cough, chest pain, and shortness of breath were present in approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 6 publications
3
43
0
Order By: Relevance
“…While prognostic factors may simply serve as severity or surrogate markers of the viral insult and/or host response, the possible pathogenic role of platelets needs to be considered. This study showed thrombocytopaenia in 36% and deranged APTT in 26% of the cohort on presentation; the former seen in 40% in the Vietnamese cohort 31 and the latter in 42.8% of Yang’s cohort 32 . Based on the finding of an elevated d ‐dimer in 45% 5 and of disseminated intravascular coagulopathy in 2.5% 33 of a smaller Hong Kong cohort, the mechanism of the observed thrombocytopaenia is likely to be consumptive in nature.…”
Section: Discussionmentioning
confidence: 65%
“…While prognostic factors may simply serve as severity or surrogate markers of the viral insult and/or host response, the possible pathogenic role of platelets needs to be considered. This study showed thrombocytopaenia in 36% and deranged APTT in 26% of the cohort on presentation; the former seen in 40% in the Vietnamese cohort 31 and the latter in 42.8% of Yang’s cohort 32 . Based on the finding of an elevated d ‐dimer in 45% 5 and of disseminated intravascular coagulopathy in 2.5% 33 of a smaller Hong Kong cohort, the mechanism of the observed thrombocytopaenia is likely to be consumptive in nature.…”
Section: Discussionmentioning
confidence: 65%
“…The use of ribavirin in adults and children has been reported by groups of investigators worldwide. 1,6,[21][22][23][24][28][29][30]35,[77][78][79][80][81][82] Ribavirin was empirically chosen in SARS because of its broad-spectrum of activities against DNA and RNA viruses. Ribavirin was also known to be effective in the treatment of fulminant murine hepatitis, which is caused by an animal coronavirus.…”
Section: Treatmentmentioning
confidence: 99%
“…The overall accuracy of the WHO guidelines for identifying suspected SARS was found to be 83% with an negative predictive value of 86% (Rainer et al, 2003). Fan et al, 2006;Hsu et al, 2003;Jang et al, 2004;Lee et al, 2003;Liang et al, 2004;Peiris et al, 2003a;Peiris et al, 2003b;Rainer et al, 2003;So et al, 2003;Tsang et al, 2003a;Tsang et al, 2003b;Vu et al, 2004;Yeh et al, 2005;Zhao et al, 2003). References for SARS in North America are Booth et al, 2003;Poutanen et al, 2003).…”
Section: Diagnosis Of Sarsmentioning
confidence: 99%